Interpreting Transnational Education Standards: The Locus of Control - Yeo, Shelley; Ling, P.; Mazzolini, M.; Giridharan, Beena; Goerke, Veronica; Hall, D.; Lueckenhausen, G. (Australian Universities Quality Agency, 2011)
Under ‘National Protocols’ established for higher education Australian universities are required to meet a consistent set of standards “regardless of whether its higher education students are located in Australia or offshore.” (MCEETYA, 2007, p.2). In this context we report in this paper approaches to curriculum and assessment decision-making encountered in an investigation of transnational education and internationalisation. The investigation is a component of the Australian Learning and Teaching Council (ALTC) project ‘Learning without borders: Linking development of transnational leadership roles to international and cross-cultural teaching excellence’; a project conducted by Curtin University and Swinburne University of Technology in Australia and in Sarawak. Meeting the same criteria specified in the National Protocols onshore and offshore can be and is addressed in different ways, even within the same higher education institution. In this paper we distinguish four approaches to curriculum decision-making designed to ensure the same standards are met. These may be styled: (a) home campus curriculum control, (b) limited branch campus learning, teaching and assessment contextualisation, (c) substantial branch campus learning, teaching and assessment contribution constrained by a requirement to attain the same learning outcomes, and (d) branch campus curriculum design. The locus of control varies between these approaches with implications for both the student experience and the professional experience and responsibilities of staff.